2022
DOI: 10.1158/1535-7163.mct-22-0323
|View full text |Cite
|
Sign up to set email alerts
|

JAK: Not Just Another Kinase

Abstract: The Janus kinase/signal transducer and activator of transcription (JAK/STAT) axis is implicated in cancer, inflammation, and immunity.Numerous cytokines/growth factors affect JAK/STAT signaling. JAKs noncovalently associate with cytokine receptors, mediate receptor tyrosine phosphorylation, and recruit STAT proteins.Tyrosine-phosphorylated STATs dimerize and are transported into the nucleus to function as transcription factors. Signaling is attenuated by specific suppressor of cytokine signaling proteins, crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…It is predominantly expressed in marrow cells, thymocytes, NK cells, activated B cells, and activated T cells. It also transduces a signal in response to its activation via tyrosine phosphorylation by interleukin receptors 25 . STAT3 was the substrate and downstream signal molecule of JAK kinase, responsible for regulating gene transcription and signal transduction 26 .…”
Section: Discussionmentioning
confidence: 99%
“…It is predominantly expressed in marrow cells, thymocytes, NK cells, activated B cells, and activated T cells. It also transduces a signal in response to its activation via tyrosine phosphorylation by interleukin receptors 25 . STAT3 was the substrate and downstream signal molecule of JAK kinase, responsible for regulating gene transcription and signal transduction 26 .…”
Section: Discussionmentioning
confidence: 99%
“…[29,30] There are 4 JAKs proteins, which can be divided into JAK1, JAK2, JAK3, and TYK2, while there are 7 STATs proteins, which can be divided into STAT1, STAT2, STAT3, STAT4, STAT5A, STAT5B, and STAT6. [31] When cells are stimulated exogenously, JAKs proteins bind to cytokine receptors in a non-covalent manner and mediate receptor tyrosine phosphorylation, which then binds to growth factor STATs to form complexes and is transported into the nucleus as a transcription factor to play a biological role. [32] Studies have shown that the main molecules involved in the pathogenesis of osteosarcoma are JAK2, TYK2, STAT1, STAT2, STAT3, and STAT5A.…”
Section: Jak/stat3 Signaling Pathwaymentioning
confidence: 99%
“…However, once IFN-I binds to IFNAR, they are automatically activated by transphosphorylation. Subsequently, JAKs promote the phosphorylation of the intracellular tails of specific tyrosine receptors, which provides a docking point for members of the STAT family of transcription factors [96]. To ensure that the signal can be properly switched off, it has been reported that suppressors of cytokine signaling (SOCS) proteins are negative feedback inhibitors of the signal cascade, which inhibit JAKs activity or target IFN-I-induced signaling components for ubiquitination and subsequent proteolysis [97][98][99].…”
Section: Jak1 and Tyk2mentioning
confidence: 99%